Comparative analysis of Optical Microscopy, Scanning Electron Microscopy, and Micro-Computed Tomography on measurements - Frederick Khalil Karam; Karla Zancope; Thiago de Almeida Prado Naves Carneiro; Murilo Navarro de Oliviera; Caio César Dias Resende; Flávio Domingues das Neves (Universidade Estadual de Campinas, 2017)
Microscopic measurements are widely used in scientific research and the correct equipment to realize these evaluations could be critical to determine study results. Regarding microscopic measurements, three of the most used methods are: Optical Microscopy (OM), Scanning Electron Microscopy (SEM), and Micro-computed Tomography (MCT). It is important to select the best method for assessing diverse parameters, considering operational characteristics of the method, the equipment efficiency, and the machinery cost. Therefore, the main objective of this study was to define which is the most useful measurement method for assessing magnitudes below 0.4 mm. Ten dental implants, with known dimensions as defined by the manufacturer were randomly distributed. Two blinded observers assessed the distance between the second and the third screw vortex of the implants using three suggested methods. The true distance was defined to be 0.5 mm. The assessed distances were: 0.597±0.007mm for OM, 0.578±0.017mm for SEM, and 0.613±0.006mm for MCT. The assessed distances were significantly different when the methods were compared (P>0.01). All measurements were into the CAD tolerances. It was possible to conclude that linear measurements between 595 and 605 μm could be performed by any of the described technologies.